The Relationship Between Workload and Nurse Satisfaction During Pandemic in the Pendalungan Jember Area - Afandi, Alfid Tri; Putri, Prestasianita (Al-Hijrah Indonesia, 2023)
Workload is an analysis process of the time used by someone in completing a job task, a disproportionate workload will have an impact on stress and can have a negative impact, namely job dissatisfaction. Objectives in this study is to see how workload related to nursing satisfaction during a pandemic in the Pendaluangan Jember area. The research design is a cross-sectional correlation description, Spearman Rho data analysis, the total population of all practicing nurses is 115 nurses with the sampling technique using the Slovin formula with a margin of error of 5% so that 112 nurses are taken as a sample (simple random sampling). The results showed that there was no relationship between workload and nurse satisfaction at the Pendalungan Jember Hospital (p=0.067). The majority's workload assessment was moderate (50%) where out of 112 nurse respondents, the majority of 84 nurses had worked > 5 years (75%), while in terms of education, the majority of Vocational Nursing graduates were 82 nurses (73.2%). Hospitals can increase nurse satisfaction by providing workloads for nurses according to the clinical authority and competence of each nurse so that the nurse's workload becomes lighter and nurse satisfaction can increase.